A new technique for determining Substorm Onsets and Phases from Indices of the Electrojet (SOPHIE). Issue 12 (14th December 2015) - Forsyth, C.; Rae, I. J.; Coxon, J. C.; Freeman, M. P.; Jackman, C. M.; Gjerloev, J.; Fazakerley, A. N.
Abstract: We present a new quantitative technique that determines the times and durations of substorm expansion and recovery phases and possible growth phases based on percentiles of the rate of change of auroral electrojet indices. By being able to prescribe different percentile values, we can determine the onset and duration of substorm phases for smaller or larger variations of the auroral index or indeed any auroral zone ground‐based magnetometer data. We apply this technique to the SuperMAG AL (SML) index and compare our expansion phase onset times with previous lists of substorm onsets. We find that more than 50% of events in previous lists occur within 20 min of our identified onsets. We also present a comparison of superposed epoch analyses of SML based on our onsets identified by our technique and existing onset lists and find that the general characteristics of the substorm bay are comparable. By prescribing user‐defined thresholds, this automated, quantitative technique represents an improvement over any visual identification of substorm onsets or indeed any fixed threshold method. Key Points: Identifies substorm expansion, recovery, and possible growth phases from magnetic indices Phases identified from percentiles of the index rate change not fixed values Technique provides greater information about substorms than existing lists